Cost Overruns in Housing Projects - Lee, See Wen; Zainal, Rozlin; Abdul Rahim, Mohd Hilmi Izwan; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2022)
Construction field plays an important role in economic growth especially the housing projects. While it is usual to see a construction project fail to meet its aims within the specified budget owing to a variety of circumstances, it is also common to see a construction project fail to meet its objectives within the specified budget due to a variety of factors. The impacts of cost overrun are implying loss of profit for non-completion, and defamation that could jeopardize his/her chances of winning further jobs, if at fault to a contractor. Thus, this research is to identify the factors that causing cost overruns in housing projects, to identify the impacts when cost overruns occur in housing projects and the method used to overcome when the cost overruns occur in housing projects. There were 210 contractors in Johor were the respondents for this research. Questionnaire form was used to carry out the research. The questionnaire form delivered through email to the respondents. The data were analysed using Statistical Package for Social Science (SPSS) software for analysed on descriptive statistic to obtain the result. After obtaining the data, the researcher can find out that poor scheduling is the main factor that causing cost overruns in housing projects. While losing profit is the main impacts when cost overruns occur in housing project. For objective 3, the researcher identifies that method correct maintenance in control of material, optimizing employee scheduling for control of labor cost and offering high quality training in control of equipment cost are the main methods to overcome cost overruns problems in housing projects. In conclusion, this research not only alert the contractors, but also helps the stakeholders, client and so on who relate to the housing projects more understanding about the factors that cause cost overruns, the impacts that cost overruns brings and the method to overcome the cost overruns issue that happened in Johor.